Islamic Ethics as a Philosophical Framework for Conflict Resolution - Ahmad Asroni (CV Putra Publisher, 2026)
This paper examines the role of Islamic philosophy, particularly Islamic ethics, as a philosophical framework for conflict resolution within contemporary societies that are increasingly pluralistic, complex, and vulnerable to social conflict. Rapid social transformation, technological advancement, globalization, and the increasing polarization of identities have contributed to the emergence of various forms of religious, ethnic, cultural, and ideological conflicts. In this context, the study aims to examine how Islamic philosophy can contribute to the prevention, resolution, and transformation of conflicts through ethical and philosophical approaches. This research employs a qualitative approach using the library research method, drawing upon both classical and contemporary literature related to Islamic philosophy, Islamic ethics, conflict resolution, and peace studies. The findings reveal that Islamic philosophy possesses rational, critical, spiritual, and humanistic characteristics capable of shaping wise individuals in responding to differences and social conflicts. Islamic ethics, which emphasizes the values of justice (‘adl), compassion (rahmah), tolerance (tasamuh), moderation (wasatiyyah), peace (sulh), and brotherhood (ukhuwwah), has proven to be highly relevant as a moral foundation for fostering reconciliation and social harmony. Furthermore, the teachings of the Qur’an and Hadith provide important principles concerning mediation, dialogue, forgiveness, and respect for human dignity as essential mechanisms for conflict resolution.